2020
DOI: 10.3390/nano10112266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Molten Salt Nanofluids for Thermal Energy Storage Application in Concentrated Solar Power Plants—Mechanistic Understanding of Specific Heat Capacity Enhancement

Abstract: Molten salts mixed with nanoparticles have been shown as a promising candidate as the thermal energy storage (TES) material in concentrated solar power (CSP) plants. However, the conventional method used to prepare molten salt nanofluid suffers from a high material cost, intensive energy use, and laborious process. In this study, solar salt-Al2O3 nanofluids at three different concentrations are prepared by a one-step method in which the oxide nanoparticles are generated in the salt melt directly from precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For a detailed discussion on the T-history method and its calculations, see ref. 43–45. In the end, the surface morphology of the nanocomposites is investigated for possible representative microstructures using scanning electron microscopy (SEM; make: Carl Zeiss Ultra 55 field-emission scanning electron microscope) with an accelerating voltage of 5 kV at the Micro and Nano Characterization Facility (MNCF), Centre for Nano Science and Engineering, IISc Bangalore.…”
Section: Methodsmentioning
confidence: 99%
“…For a detailed discussion on the T-history method and its calculations, see ref. 43–45. In the end, the surface morphology of the nanocomposites is investigated for possible representative microstructures using scanning electron microscopy (SEM; make: Carl Zeiss Ultra 55 field-emission scanning electron microscope) with an accelerating voltage of 5 kV at the Micro and Nano Characterization Facility (MNCF), Centre for Nano Science and Engineering, IISc Bangalore.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most recent initiatives to improve heat exchange and overall performance of CSPP and NPP is the addition of nano-particles, often known as nano-fluids, to the molten salts. 147,148 Nano-fluids are a new class of HTFs developed by diffusing nanoparticles (size <100 nm) in standard HTFs. 149 These nanoparticles might be organic, like fluorescent nanoparticles, or inorganic, like SiO 2 or silica, and Al 2 O 3 or alumina.…”
Section: Addition Of Nanoparticles In Molten Saltsmentioning
confidence: 99%
“…It was observed that efficiency of a TES using molten salts can be further enhanced by improving their thermo‐physical attributes. One of the most recent initiatives to improve heat exchange and overall performance of CSPP and NPP is the addition of nano‐particles, often known as nano‐fluids, to the molten salts 147,148 . Nano‐fluids are a new class of HTFs developed by diffusing nanoparticles (size <100 nm) in standard HTFs 149 .…”
Section: Addition Of Nanoparticles In Molten Saltsmentioning
confidence: 99%
“…The preferred fluid properties are important for the selected process, to facilitate the optimal combination procedure for a specific nanofluid. Consequently, it is critical to develop a collection of mixture procedures for the nanofluids' choice group, when subjected to objective properties and processes [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%